Rapamycin alleviates inflammation and muscle weakness, while altering the Treg/Th17 balance in a rat model of myasthenia gravis. Issue 4 (17th July 2017) - Jing, Feng; Yang, Fei; Cui, Fang; Chen, Zhaohui; Ling, Li; Huang, Xusheng
Abstract : Myasthenia gravis (MG) is an autoimmune disease commonly treated with immunosuppressants. We evaluated the novel immunosuppressant, rapamycin (RAPA), in a rat model of experimental autoimmune MG (EAMG). Mortality rates in the RAPA (12%) were significantly down compared with the EAMG (88%) or cyclophosphamide (CTX) (68%) intervention groups. Muscular weakness decreased after both RAPA and CTX treatment. However, Lennon scores were lower (1.74 ± 0.49, 3.39 ± 0.21, and 3.81 ± 0.22 in RAPA, CTX, and EAMG groups, respectively), and body weights (203.12 ± 4.13 g, 179.23 ± 2.13 g, and 180.13 ± 5.13 g in RAPA, CTX, and EAMG groups, respectively) were significantly higher, only in the RAPA group. The proportion of regulatory T cells (Treg) significantly increased, while that of Th17 cells significantly decreased in the RAPA group compared with the EAMG group. In comparison, CTX intervention resulted in increased Th17 but significantly decreased Tregs. Hence, RAPA can be more effectively used in comparison with CTX to treat MG, with an efficacy higher than that of CTX. In addition, our results suggest RAPA's efficacy in alleviating symptoms of MG stems from its ability to correct the Treg/Th17 imbalance observed in MG.